Does Going Tough on Banks Make the Going Get Tough? : Bank Liquidity Regulations, Capital Requirements, and Sectoral Activity - Igan, Deniz; Mirzaei, Ali. (Washington, D.C. : International Monetary Fund, 2020)
Whether and to what extent tougher bank regulation weighs on economic growth is an open empirical question. Using data from 28 manufacturing industries in 50 countries, we explore the extent to which cross-country differences in bank liquidity and capital levels were related to differences in sectoral activity around the period of the global financial crisis. We find that industries which are more dependent on external finance, in countries where banks had higher liquidity and capital ratios, performed relatively better during the crisis, with regard to investment rates and the creation of new enterprises. This relationship, however, exists only for bank-based systems and emerging market economies. In the pre-crisis period, we find only a marginal link to bank capital. These findings survive a battery of robustness checks and provide some solid support for the tighter prudential measures introduced under Basel III.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet